Orlando Tangelo - Stephen H. Futch; L.K. Jackson (EDIS, 2018)
This document is about the Orlando tangelo, a cross between Dancy tangerine and a Duncan grapefruit which was made by W. T. Swingle of the U.S.D.A. in 1911. Originally this variety was known as "Lake tangelo" but changed to "Orlando" many years ago. First time published Sep. 1993.